Pterygoid hamulus syndrome: a case report - Galvez Paul; Moreau Nathan; Fenelon Mathilde; Marteau Jean-Marie; Catros Sylvain; Fricain Jean-Christophe (EDP Sciences, 2020)
Introduction: Pterygoid hamulus syndrome (PHS) is a little-known differential diagnosis of orofacial pain. It is characterized by oropharyngeal pain, secondary to inflammatory bursitis of the tensor veli muscle of post-traumatic origin, frequently fostered by an associated hypertrophy of the hamular process. Observation: A 64-year-old female patient, type 2 diabetic, consulted for constant posterior palatal pain located near to 17, lasting for 10 years. The inspection did not reveal any mucosal lesions. Right hamulus palpation increased the pain and revealed hamulus hypertrophy. A diagnosis of PHS was evoked. Comment: A review of the literature is proposed. The treatment of PHS is initially conservative, but a surgical treatment can be proposed in case of morphological anomalies. Conclusion: PHS is a little-known syndrome whose diagnosis must be mentioned by the oral surgeon faced with chronic oropharyngeal pain. The diagnosis is clinical and radiological, the treatment is medical and/or surgical.